Genetic Diagnosis of Adult Hemodialysis Patients With Unknown Etiology - Takuya Fujimaru; Takayasu Mori; Motoko Chiga; Shintaro Mandai; Hiroaki Kikuchi; Fumiaki Ando; Yutaro Mori; Koichiro Susa; Yuta Nakano; Takao Shoji; Yuichiro Fukudome; Naoto Inaba; et al. (Kidney International Reports)
Introduction: Kidney disease of unknown etiology accounts for 1 in 10 adult end-stage renal disease (ESRD) cases worldwide. The aim of this study is to clarify the genetic background of patients with chronic kidney disease (CKD) of unknown etiology who initiated renal replacement therapy (RRT) in adulthood. Methods: This is a multicenter cross-sectional cohort study. Of the 1164 patients who attended 4 dialysis clinics in Japan, we first selected patients who started RRT between the ages of 20 and 49 years. After excluding patients with apparent causes of CKD (e.g., diabetic nephropathy, polycystic kidney disease (PKD) with family history, patients who underwent renal biopsy), 90 patients with CKD of unknown cause were included. The 298 genes associated with CKD were analyzed using capture-based targeted next-generation sequencing. Results: Of the 90 patients, 10 (11.1%) had pathogenic variants in CKD-causing genes and 17 (18.9%) had variant of unknown significance (VUS). Three patients had PKD1 pathogenic variants, and 1 patient had PKD1 and COL4A4 pathogenic variants. In addition, 2 patients were diagnosed with atypical hemolytic uremic syndrome (aHUS) due to C3 or CFHR5. One patient each was diagnosed with Alport syndrome due to COL4A4 and COL4A3 variants, nephronophthisis due to NPHP1 variants, Fabry disease due to GLA variants, and autosomal-dominant tubulointerstitial kidney disease due to UMOD variants. Genetic diagnoses were not concordant with clinical diagnoses, except for patients with PKD1 variant. Conclusion: This largest study on genetic analysis in hemodialysis-dependent adults revealed the presence of undiagnosed inherited kidney diseases.